Patient Perspectives on the Cultural Competence of US Health Care Professionals - Blewett, Lynn A. (JAMA Netw Open, 2019)
This survey study uses data from the 2017 National Health Interview Survey to examine patients’ perspectives on the cultural competence of US health care professionals.